The return of the native - Hardy, Thomas, 1840-1928 (Everyman's library, 1999)
"In his timeless story of two pairs of mismatched lovers, The Return of the Native sets romantic idealism as a destructive counterpoint to reality and disillusionment." "Against the lowering background of Egdon Heath, fiery Eustacia Vye passes her days, wishing only for passionate love. She believes that her escape from Egdon lies in marriage to Clym Yeobright, home from Paris and discontented with his work there. But Clym wishes to return to the Egdon community; a desire which sets him in opposition to his wife and brings them both to despair" "In the Introduction to this new edition, Penny Boumelha identifies the literary and classical allusions in Hardy's text, in particular the parallels with Flaubert's Madame Bovary and with the Oedipus story. In doing so she demonstrates Hardy's claim for tragic status for ordinary human lives and the ways that the characters in the novel - especially the ill-fated lovers and Damon Wildeve - spoil their chances to master their own destinies."--Jacket.